Highly Efficient and Stable Phosphorescent Organic Light‐Emitting Diodes Utilizing Reverse Intersystem Crossing of the Host Material. Issue 11 (4th August 2014) - Fukagawa, Hirohiko; Shimizu, Takahisa; Kamada, Taisuke; Kiribayashi, Yukihiro; Osada, Yoshichika; Hasegawa, Munehiro; Morii, Katsuyuki; Yamamoto, Toshihiro
<x xml:space="preserve">Abstract</x> Phosphorescent organic‐light emitting diodes (PHOLEDs) exhibit an internal quantum efficiency of 100% and their early practical realization is expected. One of the main challenges in PHOLEDs is to improve the operational stability of green and blue devices. Triplet exciton dynamics in stable PHOLEDs, which are different from those in unstable PHOLEDs, are shown. An efficient and stable green PHOLED is demonstrated by employing a suitable host that surrounds the phosphorescent dopant. The transient photoluminescence characteristics show that the triplet excitons of the host, which are generally unstable, are rapidly transferred to the dopant and emit phosphorescence in the stable PHOLED. Most of the triplet excitons of the host in the stable PHOLED are transferred to the dopant within 10 ns, following the Förster process by utilizing reverse intersystem crossing from the triplet state to the singlet state. The findings also provide a design strategy for hosts to enable realization of highly stable full‐color PHOLEDs.